PERTIMBANGAN HAKIM DALAM PUTUSAN AKIBAT PERCERAIAN TERKAIT HARTA BAWAAN ISTRI YANG DIJADIKAN JAMINAN PELUNASAN HUTANG DALAM PERKAWINAN - Siti Yeri Rezyu Wahida; IWP Sucana Aryana (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2021)
Marriage is a legal act that creates rights and obligations for the individuals who do it. A man and a woman after marriage will have legal consequences regarding marital property and their income. Problems that often occur in marriage are legal consequences that arise when a divorce is carried out in court. It will be a problem if in marriage there is no gono-gini and leave debt by using collateral from the wife's innate property. To provide justice and legal certainty to these problems, the judge must be careful and wise. The type of research used in this research is normative legal research. The technique of collecting legal materials used by the author in this research is library research. This study uses a stattue approach, and a conceptual approach. If the wife's property is used as a guarantee for paying off debt on behalf of the wife, then the guarantee remains the wife's innate property and the wife is fully entitled to take legal actions on her property. In the event that there is a debt during the marriage, the husband is fully responsible for the settlement of joint debts made by the wife, except for this responsibility, namely the settlement of debts made before the marriage by the wife, which responsibility ends with the implementation of the division and separation of mixed assets.